Deactivation of nitrogen donors in silicon carbide - Schmid, Frank; Pensl, Gerhard; Bockstedte, Michel Georg; Mattausch, Alexander; Pankratov, Oleg; Ohshima, T.; Itoh, H.; Weber, Heiko B.; Reshanov, Sergey (Physical Review B, 2006)
Hexagonal SiC is either co-implanted with silicon (Si+), carbon (C+), or neon (Ne+) ions along with nitrogen (N+) ions or irradiated with electrons (e-) of 200 keV energy. During the subsequent annealing step at temperatures above 1450°C a deactivation of N donors and a reduction of the compensation are observed in the case of the Si+/N+ co-implantation and e- irradiation. The N donor deactivation is investigated as a function of the concentration of the co-implanted species and the annealing temperature. The formation of energetically deep defects is analyzed with deep level transient spectroscopy. A detailed theoretical analysis based on the density functional theory is conducted; it takes into account the kinetic mechanisms for the formation of N interstitial clusters and (N-vacancy) complexes. In accordance with all the experimental results, this analysis distinctly indicates that the (NC) 4 - VSi complex, which is thermally stable at high temperatures and which has no level in the band gap of 4H-SiC, is responsible for the N donor deactivation. © 2006 The American Physical Society.
UnivIS-Import:2015-04-14:Pub.2006.nat.dphy.IAP.LAP.deacti

Nonperturbative theory of effective Hamiltonians for deformations in two-dimensional materials: Moire systems and dislocations - Rost, Fabian; Gupta, R.; Fleischmann, Maximilian; Weckbecker, Dominik; Ray, Nicolas; Olivares, J.; Vogl, Michael; Sharma, S.; Pankratov, Oleg; Shallcross, Sam (Physical Review B, 2019)
We demonstrate that there exists a continuum Hamiltonian H(r, p) that is formally the operator equivalent of the general tight-binding method, inheriting the associativity and Hermiticity of the latter operator. This provides a powerful and controlled method of obtaining effective Hamiltonians via Taylor expansion with respect to momentum and, optionally, deformation fields. In particular, for fundamentally nonperturbative defects, such as twist faults and partial dislocations, the method allows the deformation field to be retained to all orders, providing an efficient scheme for the generation of transparent and compact Hamiltonians for such defects. We apply the method to a survey of incommensurate physics in twist bilayers of graphene, graphdiyne, MoS2, and phosphorene. For graphene we are able to reproduce the "reflected Dirac cones" of the 30 degrees quasicrystalline bilayer found in a recent angle-resolved photoemission spectroscopy experiment, and we show that it is an example of a more general phenomenon of coupling by the moire momentum. We show that incommensurate physics is governed by the decay of the interlayer interaction on the scale of the single-layer reciprocal lattices, and demonstrate that incommensurate scattering effects lead to a very rapid broadening of band manifolds as the twist angle is tuned through commensurate values.
CRIS-Team WoS Importer:2021-10-18

Theory of condensed matter (in memory of Yurii Vasil'evich Kopaev) (Scientific session of the Physical Sciences Division of the Russian Academy of Sciences, 13 December 2017) - Andreev, A. F.; Zvezdin, A. K.; Lozovik, Yu E.; Pankratov, Oleg; Tikhodeev, S. G.; Gorbatsevich, A. A. (Physics-Uspekhi, 2018)
CRIS-Team WoS Importer:2019-08-09

Tuning topological surface magnetism by bulk alloying - Klier, Nicolas; Sharma, S.; Rost, Fabian; Pankratov, Oleg; Shallcross, Sam (Physical Review B, 2019)
Deploying an analytical atomistic model of the bulk band structure of the IV-VI crystalline topological insulators, we connect the spin structure of the surface state to the crystal field and spin-orbit coupling parameters of the bulk material. While the Dirac-Weyl-type topological surface state is often assumed to be universal, we show that the physics of the surface state is strikingly nonuniversal, carrying a profound imprint of the bulk physics. To see this explicitly we calculate the Ruderman-Kittel-Kasuya-Yosida interaction, which may be viewed as a probe of this surface state spin structure, finding that its qualitative form depends on the values the bulk spin-orbit and crystal field parameters take. This opens the way to tune the spin interaction on the surface of a IV-VI topological insulator by, for instance, varying the composition of the IV-VI ternary compounds.
CRIS-Team WoS Importer:2021-10-18